A comparison of medical record with billing diagnostic information associated with ambulatory medical care. - Studney, D R (1981)
The degree of similarity between diagnostic information furnished with claims and that simultaneously entered into the medical record was estimated for 1,215 private office visits in British Columbia, Canada. For each visit, claim card and chart diagnoses were compared by having three independent internists (blinded to source and type of the data) make judgments about each diagnostic pair. The judges were highly consistent internally and their judgments were stable over time. In 40 per cent of cases chart and claims data were judged dissimilar, and in 38 per cent of cases claims data were judged more valuable as a reflection of the primary problem treated. The degree of judged similarity of chart and claims data correlated significantly and negatively with physician workload, income, and judges' preference for the billing card diagnosis. We conclude that in using claims data to determine the content of ambulatory visits, independent validation of such data may be important.